Efeito de filmes de quitosana e bentonita na conservação pós-colheita de banana prata (Musa spp.) - Medeiros, Silvia Valeria de (2020)
Bananas are the most consumed fruit in Brazil and in the world. However, about 40% ofproduction is lost due to earlyripening. Studies with edible coatings based on biopolymers, such as chitosan, are important to extendthe shelf life of fruitsand some ofits limitations can be minimized by incorporating clay. This work aimed to evaluate the postharvest conservation of prata bananas coated with biopolymeric and clay-biopolymeric coverings. The first stage characterized the films and the second evaluated the post-harvest conservation of bananas coated with coatingswith better physical characteristics. Six films were prepared and characterized: three biopolymeric, with concentrations of chitosan at 0,5, 1,0 and 1,5% and glycerol at 15%(m/m), and three clay-biopolymeric ones, prepared with the addition of bentonite at 0,2%(m/V) to the formulations of biopolymeric films -FBP1, FBP2 and FBP3; FABP1, FABP2 and FABP3, respectively. Morphology, chemical composition, microstructure of the surface, disposition of the bentonite in the polymeric matrix, thermal decomposition and water vapor permeability were analyzed. The evaluation of post-harvest conservation of coated fruits was carried out with physical-chemical, physical, microbiological and sensory analyzes, in addition to photographic and disease incidence records, during a period of 9 to 11 days of storage, at room temperature (24,05 ºC ± 1,29). The characterization showed greater surface uniformity in the biopolymeric films and the presence of roughness on the surface of the biopolymeric clay, attested to the presence of bentonite in the biopolymeric clay films and evidenced predominantly amorphous material without noticeable changes with the insertion of the bentonite. Vibrational bands characteristic ofbonds and groups existing in chitosan were observed in biopolymeric films, in addition to those characteristics of bonds and groups existing in the structure of bentonite, in biopolymeric clay films. The addition of clay resulted in greater residue formation after thermal decomposition of the material and enhanced the barrier property against water vapor permeability. FABP3 was the film that presented greater thickness, less permeability to water vapor and less loss of mass related to the thermal decomposition of the polymer. The bananas were coated with chitosan coatings at 1,0%, without (BP1,0%) and with clay (ABP1,0%) and 1,5%, without (BP1,5%) and with clay (ABP1,5%) and compared to the control group. At the end of the storage period, the BP1,5% group had less (p < 0,05) content of total soluble solids, less (p < 0,05) loss of mass and greater (p < 0,05) thickness of the peelthat 11control it. BP1,5% and ABP1,5% had lower values of acidity and pulp / peel ratio (p < 0,05) than the control and greater firmness (p < 0,05), throughout storage. The coatings of the ABP1,5% and BP1,5% groups delayed ripening and increased the postharvest life of bananas by 2 and 4 days, respectively. It was also found that all groups were within the minimum microbiological standards required by current legislation and that the coatings did not alter the sensory characteristics of the banana. Therefore, 1,5% chitosan coverings, with and without bentonite, were more efficient in delaying ripening and prolonging the life of bananas